PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS X TKR 1 SMK TELKOM PEKANBARU - Nurina Puspa Dewi Puspa Dewi Dewi; Susda Heleni Heleni; Syofni ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research isa classaction research to make learningprocess be better and to improve mathematic learning result by applying Cooperative LearningTalking Stick Model. The subjects werestudents of class XTKR1SMKTelkomPekanbaruinthe second semester ofthe academic year2013/2014, whichamounted to22people and all aremenwithheterogeneouscapabilities. This studyconsistedoftwocycles, eachcycleconsistingoffourphases, namelyplanning, action ,observationandreflection. Eachend of the cyclecarried outdaily tests. Data collected throughobservationandtestsin the form ofdaily tests. Data was analyzed usingdescriptivestatisticalanalysis. Resultsof researchonthe observationsheetshows theactivityof teachers and studentshave beenperforming wellafterdoingthe action. Based on theobservations of researchersduringthe learningprocessinclassXTKR1SMKTelkomPekanbaru, seenmost studentsexcitedandparticipatorylearning processcarried out, such asin response toapperception, presented the results offocus group discussions, responding to the presentation, the implementation of theTalking Stick, deliveringconclusion, doLKSandanswer thegroup of theiractivitieswith friends. Students aretrying to completethe activitiesinLKSwell. Actionis successfulifthe number of studentswhoachievea score ofKKMonthe basis ofincreasingthedaily testsI andIIdaily tests. The percentage ofstudentswhoachievea score ofKKMonbasic, daily testI (first cycle), daily testII(second cycle) respectivelyare13.6%, 45.5%, and63.6%. Penilitianresultsshowed thatthe application ofcooperative learning modelTalking Stickcanimprovethe learningprocessandimprove learning outcomesmathclass XTKR1SMKTelkomPekanbaru. Key words:Mathematics learning outcome, cooperative learning, Talking Stick, Class action research.